A rare case of giant mucinous cystadenocarcinoma of the right ovary with metastatic deposits and Brenner tumor in the left ovary - Kandhalu, Salini Krishnrao; Sameeraa, Pappu RSS; Mohan, KV Murali; Jayalakshmi, Medikonda (Indian Journal of Case Reports, 2024)
Ovarian cancer is the second most common gynecological malignancy. Mucinous tumor accounts for 3% of ovarian tumors and is a challenging task for a surgical pathologist. Association of Brenner tumor, a subtype of epithelial malignancy is a rare entity reported in the literature. Herein, we report a unique case of a 57-years old post-menopausal woman who presented with progressive abdominal distention for 3 years and constipation for 1 year. Clinically, it was suspected as a case of complex ovarian cyst and the patient underwent staging laparotomy. Intraoperatively, a giant mucinous cystadenocarcinoma of the right ovary with deposits in the pouch of Douglas, omentum, umbilical, and the sub-umbilical region was found along with a benign Brenner tumor of the left ovary.